Cardiovasculoprotective Effects of Estrogen and its Use as Hormonal Replacement Therapy - Didik Supriyadi Kusumo Budoyo; Hemi Sinorita (Journal of World Science, 2024)
Epidemiologic studies have shown that the incidence of cardiovascular disease is closely related to gender. This is because endogenous estrogens have broad effects on the circulatory system, leading to the hypothesis that estrogens are cardiovascular protective, underlying their use as hormone replacement therapy (HRT) to reduce the incidence of cardiovascular disease. However, large prospective clinical trials (HERS and WHI) do not support this. This review aims to better understand the cardiovascularoprotective effects of estrogen and answer the question of whether estrogen can be used as hormonal replacement therapy in post-menopausal women to prevent cardiovascular events by incorporating data from the most recent prospective clinical trial, the KEEPS study. HERS and WHI reported no reduction in cardiovascular events in postmenopausal women using HRT, even showing an increased risk of thromboembolism. This study was criticized because participants had been menopausal for 12 years, so the KEEPS study was conducted with participants within three years of menopause, with the result that there was no significant reduction in the progression of atherosclerosis between the HRT group and the placebo group. The KEEPS study states that HRT is safe, and no thromboembolic events were found. Although endogenous estrogen has cardiovascular protective effects, estrogen hormone therapy cannot reduce cardiovascular events in postmenopausal women despite metabolic improvements and beneficial effects such as improvement of postmenopausal-related symptoms, maintaining bone density, and improving sexual function.